Design of a nursing psychoeducation program to reduce preoperative anxiety in adults - Oliveira, Palmira; Pires, Regina; Silva, Rosa; Sequeira, Carlos (Frontiers in Public Health, 2024)
Introduction Preoperative anxiety, with its multifactorial origins, affects a wide range of surgical patients, leading to adverse physiological and psychological effects in the perioperative period. Customized, autonomous nursing interventions are needed to address individual person needs. The shift toward outpatient surgery emphasizes the need for restructured nursing approaches. Existing literature suggests that preoperative nursing consultations offer opportunities for assessing needs, providing information, and prescribing anxiety-reduction strategies. Psychoeducation, a specialized skill within mental health and psychiatric nursing, has proven effective in alleviating preoperative anxiety and reducing postoperative complications. The aim is to obtain and analyze the information reflecting nurses’ understanding of the design, structure, and operationalization of a psychoeducation program to reduce preoperative anxiety in adults. Methods A qualitative, exploratory, descriptive study was conducted. Data were collected through a 90-min focus group session held online via Zoom Meetings videoconferencing platform. Inclusion criteria for the participant’s selection were established. The focus group was guided to deliberate on potential strategies for crafting effective psychoeducational interventions. Data collection ceased upon reaching theoretical saturation and gathered information was submitted for content analysis. Ethical procedures were ensured. Results Of the participants, 10 were specialist nurses (7 working in mental health and psychiatric nursing and the remaining in medical-surgical nursing), with an average age of 41 and an average of 15 years working in surgical services. The nurses selected the target population, the structure and content of the psychoeducation sessions, and the resources and addressed the perceived importance, effectiveness, and feasibility of the designed psychoeducation program. Discussion The study revealed the nurses’ understanding of the design of a psychoeducation program potentially effective in reducing preoperative anxiety in adults, in an outpatient surgery context. This result will allow the transfer of the produced knowledge to nurses’ professional practice reflecting lower levels of anxiety and promoting a better surgical recovery. This is an unprecedented study conducted in Portugal, adding substantial knowledge to the nursing discipline. However, further research into implementing psychoeducation in a surgical context is suggested aiming to consolidate the results of research already carried out internationally.